Economic Transition and Social Protection : Issues and Agenda for Reform - Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 1998)
This paper briefly describes the factors constraining the social protection policies in the Baltics, Russia, and other countries of the former Soviet Union (BRO). The analysis considers public spending in social programs, including generalized subsidies for goods and consumer services, pensions, unemployment-related and social benefits, and education and health care. The paper then lists policies that can help mitigate the worsening living standards of the poor and the vulnerable in a fiscally sustainable manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet